2019
DOI: 10.1021/acs.est.9b00637
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neuro-Dopamine Homeostasis in Juvenile Female Atlantic Cod (Gadus morhua) Exposed to Polycyclic Aromatic Hydrocarbons and Perfluoroalkyl Substances

Abstract: The dopaminergic effect of PAH and PFAS mixtures, prepared based on environmental levels has been studied in juvenile female Atlantic cod (Gadus morhua). Benzo[a]pyrene, dibenzothiophene, fluorene, naphthalene, phenanthrene and pyrene were used to prepare a PAH mixture, while PFNA, PFOA, PFOS and PFTrA were used to prepare PFAS mixture. Cod were injected intraperitoneally twice, with either a low (1x) or high dose (20x) of each compound mixture or various combinations. After two week of exposure, levels of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…PFAS have been detected in soils, 1,2 sediments, 3 groundwaters, 4 rivers, 5 drinking water, 6 and waste water treatment plants. 7 The list of biological systems in which PFAS have been detected include humans, 8-10 sh, 11,12 birds, [13][14][15] frogs, 16 polar bears 17 and marine organisms. 18,19 The data in the peer-reviewed literature documenting the transformation and metabolic pathways of PFAS have not been captured in a systematic manner that readily supports prediction of the transformation products and metabolites of PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…PFAS have been detected in soils, 1,2 sediments, 3 groundwaters, 4 rivers, 5 drinking water, 6 and waste water treatment plants. 7 The list of biological systems in which PFAS have been detected include humans, 8-10 sh, 11,12 birds, [13][14][15] frogs, 16 polar bears 17 and marine organisms. 18,19 The data in the peer-reviewed literature documenting the transformation and metabolic pathways of PFAS have not been captured in a systematic manner that readily supports prediction of the transformation products and metabolites of PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Khan et al (2019) showed that exposure to environmentally relevant mixtures of PAHs and PFAS could modulate the neuro-dopamine homeostasis in female Atlantic cod. In addition, Dale et al…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that exposure to PFAS/BaP binary mixtures altered CYP-like activity in vivo; however, those alterations were not observed in vitro. Previous studies have indicated that mixtures of PFAS and PAHs have the potential to alter biological processes in sh(Dale et al, 2020;Horvli, 2020;Khan et al, 2019). For instance,Khan et al (2019) demonstrated female Atlantic cod (Gadus morhua) exposed to mixtures of PFAS and PAHs in vivo had altered dopaminergic signaling, including the modulation of dopamine biosynthesis, catabolism, and its receptor expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bap has been proved to rapidly distribute in the organism after being inhaled 1 and induces oxidative stress and inflammation in pulmonary, 2 liver, 3 and neuronal systems. 4 However, the form in which it interacts with the biological system has seldom been seriously interpreted. In previous laboratory-based toxicity studies, Bap was usually treated as welldispersed, single molecules in aqueous solutions as normal soluble molecules or ions.…”
Section: Introductionmentioning
confidence: 99%